2020
DOI: 10.3390/catal10111266
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Immobilized Lipase on Silica Clay as a Potential Biocatalyst on Synthesis of Biodiesel

Abstract: Biodiesel offers an important alternative to fossil fuel. In this work, Eversa Transform 2.0 lipase was immobilized onto 3-aminopropyltriethoxysilane (APTES) modified silica clay (SC) by glutaraldehyde. The characteristics of the functionalized supports and the immobilized lipase were investigated by FTIR, TEM, BET, and XRD. The results show that the optimal conditions of lipase immobilization are as follows: 2% glutaraldehyde concentration, 15 mg/mL lipase concentration and incubating at 25 °C for 60 min. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Pure SC contains a small amount of N and C, which indicates that the silica clay used contained certain organic components. 31 Compared to pure SC, the elemental contents of N, C, and H of A-SC, Glu-A-SC and Pep-Glu-A-SC increased signicantly, which should be attributed to the successful introduction of APTES. Furthermore, aer immobilization with pepsin, 0.08% of elemental S content could be observed on Pep-Glu-A-SC, illustrating that the sulfur-containing pepsin was successfully immobilized onto the support.…”
Section: Characterization Of Immobilized Pepsinmentioning
confidence: 90%
“…Pure SC contains a small amount of N and C, which indicates that the silica clay used contained certain organic components. 31 Compared to pure SC, the elemental contents of N, C, and H of A-SC, Glu-A-SC and Pep-Glu-A-SC increased signicantly, which should be attributed to the successful introduction of APTES. Furthermore, aer immobilization with pepsin, 0.08% of elemental S content could be observed on Pep-Glu-A-SC, illustrating that the sulfur-containing pepsin was successfully immobilized onto the support.…”
Section: Characterization Of Immobilized Pepsinmentioning
confidence: 90%
“…2 Effect of different molar ratios of alcohol on the sunflower oil transesterification reaction using Eversa® Transform immobilized on Sepabeads C-18 with ethanol using 10 wt% immobilized lipase using 4: 1 (E:O) molar ratio. According to the literature, several studies of enzymatic esters production, using alcohol and oil as substrates, exhibit optimal molar ratio oil:alcohol 1:3 [42][43][44][45][46][47] or 1:4 [10,11,15,[48][49][50][51].…”
Section: Effect Of Molar Ratio Alcohol In the Transesterification Of Sunflower Oil Catalyzed By Sepabeads-eversa Lipasesmentioning
confidence: 99%
“…Glutaraldehyde-activated supports and its immobilization process with lipase were described in our previous report [26]. Briefly, 1.0 g of the modified silica clay was dispersed in 10 mL of glutaraldehyde solution at 30 • C for 2 h with gentle shaking.…”
Section: Immobilization Of Lipasementioning
confidence: 99%
“…In our previous study, the cheap and easily obtained silica clay showed good performance as lipase immobilization support for biodiesel production [26]. Herein, a series of silica coupling agents with various lengths of alkyl chain was coupled with silica clay for the synthesis of a series of novel alkyl-modified silica clay support to impart the support with different degrees of hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%